Learning with Problem Solving Approach as Efforts to Improve the Ability of Mathematical Connection of Students in Accounting Study Programs in Bandung - Hidayat, Rachmat; ., Ignatius; Dianita, Mirna; Hadian, Niki (International Journal of Engineering and Technology, 2018)
The mathematics learning outcomes of accounting study program students in Bandung are still low. For this reason, efforts are needed to improve the mathematics learning outcomes of accounting study students in Bandung. One of the efforts that was taken was by increasing the ability of students' mathematical connections. In order for students' mathematical connection capabilities to increase, an alternative learning is needed namely learning using a problem-solving approach. The population in this study were students of study program in Bandung, while the sample in this study was the first semester students at Widyatama University who were randomly selected according to class. The instrument used in this study is a mathematical connection ability test in the form of a description, and a Likert scale of student attitudes. From the results of the test of the mathematical connection ability test, it was found that the test had high reliability. The validity of the item is high, the distinguishing power is quite good, and the difficulty level is moderate. Based on the results of the analysis of research data, it is known that students who obtain learning with a problem-solving approach have better connection capabilities when compared to students who obtain conventional learning. In general, student responses are positive.Â Â